A new species of Spigelia L. (Loganiaceae) from Mexico - Islas-Hernández, C. Sofia; Lozada-Pérez, Lucio; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2017)
A new Mexican species of Spigelia (Loganiaceae), distributed in the states of Guerrero and Michoacán, is here described. The new species can be distinguished from the similar-looking S. humboldtiana by its corolla with innerly purple lobes, inserted stamens above the proximal half of the corolla tube and exserted style. With this contribution, Mexico reaches a total of 20 species, of which 50% are endemic, highlighting this country as a center of diversity for this genus. A dichotomous key for the species recorded in the states of Guerrero and Michoacán is included.